Chemical properties and enzyme activity in a sewage sludge-treated soil - de Melo, W. J.; Marques, M. O.; Ferreira, M. E.; de Melo, GMP; de Melo, V. P. (Marcel Dekker Inc, 2002)
A soil sample was taken from the top 0-20cm at Jaboticabal county, São Paulo State, Brazil, air dried, sieved to 5mm, and placed into pots (2700g per pot). Sewage sludge was air-dried, ground to 2mm, and thoroughly mixed to the top 0-10cm soil of each pot, which were irrigated with distilled water in a total volume equivalent to the last 30years average rainfall in the region. Sorghum was sowed 120days after sewage sludge incorporation and then the irrigation was made according to the plants' requirement. When the plants were about 10 cm high, they were thinned to two per pot. Soil samples (0-10, 10-20, and 20-30 cm depth) were obtained immediately after the incorporation of sewage sludge and at 30, 60, 120, and 170 days after, air dried, sieved to 2 mm and analyzed for organic matter (OM), pH (0,01 mol L-1 CaCl2), extractable P (resin), potassium (K), calcium (Ca), and magnesium (Mg), amylase and cellulase activity. Sewage sludge increased soil OM, pH, extractable phosphorus (P), K. Ca. amylase and cellulase activity, especially at the rate 16 t ha(-1). Organic matter, extractable P, K, Ca, Mg. and amylase activity were higher in the top 0-10cm, while pH was higher in the 20-30cm layer. Amylase activity was not affected by sampling depth. Organic matter, pH, extractable P. K, Ca, and Mg decreased during the experimental period. Amylase activity decreased until sorghum was sowed and increased afterwards. Cellulase activity increased until 90 days after sewage sludge application and then decreased. Sewage sludge used in the experiment should already contain some amylase activity or a substance that was a soil enzyme activator and also a substance that was an inhibitor of soil cellulase inhibitor. Sonic of the plant nutrients contained in sewage sludge, mainly P, did not migrate down the soil column. an indication that sewage sludge should be incorporated into the soil to improve nutrient bioavailability. Sorghum roots increased amylase activity but did not affect cellulase activity.
Keywords: Amylases; cellulase; residue; wastewater; Soil fertility; urban waste